Reproductive Behaviour Of Timor Deer (Rusa Timorensis) - Daud Sansudewa; S.S. Capitan (Indonesian Center for Animal Research and Development, 2011)
Timor deer (Rusa timorensis) is a newly domesticated animal in Indonesia and other countries in the world. It is a potential source of meat and livelihood. Low birth rate is a problem of deer farming in Indonesia. It happens because of low concern for key aspects of behaviors including reproductive behavior. The aim of this review is to give information about reproductive behavior of Timor deer in natural habitat and captivity breeding. Libido and estrous behaviors of Timor deer in captivity breeding were similar with natural habitat. However, male Timor deer in captivity breeding took longer time to approach the females before mating, compared with those in their natural habitat. Aggressive behavior commonly leads mating. Parturition and maternal behavior of hinds are affected by limitation of space, therefore dividing the area of cage which depends on age and physiological status is needed to improve reproductive management. Key words: Reproductive behavior, captivity, Timor deer